EXAMINATION OF THE PHYSICAL ACTIVITY OF THE ELDERLY DURING THE COVID-19 EPIDEMIC - Dergez, Teodóra; Laczkó, Tamás (Stadium - Hungarian Journal of Sport Sciences, 2024)
Physical activity can be used for any movement/exercise involving energy expenditure. Scientific research discusses the issue of older adults’ physical activity. It is a common principle that an active lifestyle positively impacts older adults’ quality of life and life expectancy. During the period of the coronavirus, it was revealed in many countries that the time spent on physical activity decreased significantly due to social distancing measures. Due to the pandemic, there have been significant changes in the society’s sports consumption habits. Our research aims to examine and present the changes in the physical activity of the age group above 60 before the coronavirus and during the period of restrictions and quarantines due to the COVID-19 pandemic. For the analysis, we used data examining the first three waves of the COVID-19 epidemic collected by the Physical Activity Research Group of the Faculty of Health Sciences of the University of Pécs. In the examined periods, a "U"-"-shaped trend can be observed in the development of the physical activity of the 60-69 years age group. In the pre-coronavirus period, the level and intensity of the weekly physical activity of older adults began to decrease after the introduction of the lockdowns. Then, they continued to increase during the successive epidemic waves. The average duration of physical activity (minutes/week) at the second wave and the intensity of physical activity (METs) exceeded the pre-pandemic state significantly by the time of the third wave. As physical activity started to increase in the 60-69 age group during the second and third wave of the coronavirus, it would be essential to maintain an active lifestyle in the later period as well. Physical activity benefits people of all ages and can reduce the burden on the healthcare system.